Cancer incidence among creosote-exposed workers. - Karlehagen, S.; Andersen, Aage; Ohlson, C. G. (Scandinavian Journal of Work, Environment & Health, 1992)
Cancer incidence was studied among 922 creosote-exposed impregnators at 13 plants in Sweden and Norway. The subjects had been impregnating wood (eg, railroad cross-ties and telegraph poles), but no data on individual exposures were available. The study population was restricted to men employed during the period 1950-1975, and their cancer morbidity was checked through the cancer registries. The total cancer incidence was somewhat lower than expected, 129 cases versus 137 expected [standardized incidence ratio (SIR) 0.94]. Increased risks in both countries combined were observed for lip cancer (SIR 2.50, 95% confidence interval (95% CI) 0.81-5.83), skin cancer (SIR 2.37, 95% CI 1.08-4.50), and malignant lymphoma (SIR 1.9, 95% CI 0.83-3.78). Exposure to sunlight may have contributed to the risk of lip and skin cancer. The small number of cancer cases does not permit valid conclusions. The findings indicate that impregnating wood with creosote in earlier decades increased the risk of skin cancer.